China’s integration in the Asia-Pacific regional economic cooperation - Wei, Junhua; Gao, Yue; Elahi, Ehsan (Frontiers in Psychology, 2022)
China is actively deepening integration into economic cooperation in the Asia-Pacific region. The Regional Comprehensive Economic Partnership Agreement (RCEP) has come into force and China is one of its members. Furthermore, China is applying to join the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP). This study uses the Global Trade Analysis Project (GTAP) model to measure the impact of the RCEP and CPTPP on Gross Domestic Production (GDP), import, export, terms of trade, and social welfare of major economies under various scenarios, as well as the competitive effects and complementarity of the RCEP and CPTPP. We found that the CPTPP with China’s accession and the RCEP will complement and strengthen each other and that the members of the two agreements can obtain substantial benefits. If China and the United States join the CPTPP, China’s import growth rate will be higher than its exports. This would transmit growth to other nations and help bridge the trade gap between China and the United States.